Evaluating the Impact of Pharmacist Counselling for Asthmatic Children at Karbala Teaching Hospital for Children: An Interventional Prospective Study (Conference Paper )# - Mohammed Al-Musawi; Zinah M. Anwer (College of Pharmacy University of Baghdad, 2022)
Asthma is one of the most common chronic, non-communicable diseases affecting children worldwide. The estimated prevalence of pediatric asthma in Iraq is 15.8%. Physiologic, inflammatory and structural factors contribute to the development of asthma. Assessment and monitoring of asthma control can be done by a validated children asthma control test (CACT). Management of asthma must address three components which are an appropriate management plan, the most appropriate medication if necessary, and the use of safe and effective medication. The management plan should consider patient counseling and education about the definition of asthma, signs, and symptoms, the pathophysiology of asthma, common triggers for asthma and how can avoid them, what are the rescue medication and the controller one, proper inhaler techniques, and how to monitor asthma control. Patient education accounts for 90% of success and this can be achieved by an active collaboration among health care providers. This is a prospective interventional study that aims at evaluating pharmacist counseling for asthmatic children. The study involved 105 participants whose consent was taken and underwent a face-to-face interview about asthma counseling and inhaler technique for those who use it. Ninety-two eligible participants remained. Their CACT was recorded at the first visit and then followed up weekly for one month either by phone or physical to assess asthma control. In the fourth week, a CACT was recorded and compared to the first one before intervention. There was a significant improvement in CACT after providing the counselling and weekly follow up.